TRACKING MOLECULAR RESPONSE OF TYROSINE KINASE INHIBITORS THERAPY IN CHRONIC MYELOID LEUKEMIA PATIENTS USING RT-PCR PROFILING OF BCR-ABL TRANSCRIPTS - *Hafiz Muhammad Arsalan1,2, Amina Arif1, Muhammad Khalil Ahmad Khan3, Fatima Muccee4, Uraiimov Elaman Toktobolotovich5, Usman Wajid1, Mohsin Abbas6, *Shafia Arshad6 (Chelonian Research Foundation, 2023)
Chronic myeloid leukemia (CML) results from the formation of the Philadelphia chromosome by translocation between chromosomes 9 and 22, creating the BCR-ABL fusion oncogene. This study analyzed specific BCR-ABL transcript variants in 30 Pakistani CML patients to detect common fusion protein isoforms. RNA extraction, cDNA preparation, primer design and real-time PCR were utilized to profile three transcript variants (b3a2, b2a2, e1a2) which translate to fusion proteins p210 and p190. The b3a2 and b2a2 transcripts for p210 were detected in all 30 CML patients (100%). Additionally, 2 out of the 30 patients (6.6%) simultaneously exhibited e1a2 transcripts coding for p190. In conclusion, the major BCR-ABL fusion transcript identified in Pakistani CML cases is the b3a2/b2a2 subtype producing p210 fusion protein. A smaller subset shows co-expression of the minor e1a2 variant encoding p190. These findings help characterize the prevalence of distinct BCR-ABL isoforms within the native CML patient population. Further investigation of genotype-phenotype correlations may aid prognostic classification and treatment decisions for these patients. Key Words: CML, PCR, real time PCR, Fusion transcripts, TKI’s.